Analisis Kompetensi Guru terhadap Penyusunan Perangkat Pembelajaran pada Kurikulum Merdeka di Sekolah Dasar - Kharisma Romadhon; Irfan, Irfan (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2025)
The objective of this study is to depict teacher competence in creating educational materials within the independent curriculum at primary schools. This research employs a qualitative descriptive approach and utilizes both primary and secondary data sources. Data gathering methods consist of observations and interviews. The outcomes of the study of the research can be found that teacher competence in compiling learning tools in the independent curriculum can be described through five aspects, namely: 1) The teacher's knowledge aspect which discusses teaching ability and mastery of the material. 2) Aspects of teacher skills related to student interaction and involvement in preparing learning tools and their learning styles. 3) Attitude and behavioral aspects where the role of the teacher is crucial in establishing an effective and conducive learning atmosphere and is able to facilitate the student learning process. 4) The context aspect is associated with enhancing teacher professionalism and the use of technology as a learning support tool. 5) The evaluation aspect is related to developing student assessments and measuring understanding with rubric assessments.